Implementation of The MUI’s Fatwa No.14/2020 Concerning Worship During Pandemic: Study on Muslim Society in Ternate - Jenjang Waldiono; Muhammad Hilali Basya (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2021)
This article describes how Muslims deal with fatwa through examining the extent to which Muslims in Ternate (North Maluku) respond to MUI’ fatwa concerning the application of ibadah (worship) during the Covid-19 (Coronavirus) pandemic. In order to control and prevent the infection of the virus widely, people are required to stay at home and to keep their distance from crowds, including attending congregational worship (shalat jamaah) in mosques as issued in the MUI’s fatwa. The fieldwork was conducted in Ternate between March-May 2021, using qualitative research methods through participatory observation and interview. This article shows that the obedience of Muslim society in Ternate to the MUI’s fatwa is not only determined by aspects of the religious authority of the MUI, but also by local government, local religious leaders, and pragmatic considerations of the society as well as their perception about the dangerous impact of the Covid-19.